Accelerated Remote Consultation Tele-POCUS in Cardiopulmonary Assessment (ARCTICA) - Jeffrey Lam; Sherwin Wong; Nicholas Grubic; Salwa Nihal; Julia E Herr; Daniel J Belliveau; Stephen Gauthier; Steven J Montague; Amer Johri (CINQUILL Medical Publishers Inc., 2020)
The ability of point-of-care ultrasound (POCUS) to provide rapid and accurate bedside assessment of both the heart and lungs allows it to be a powerful tool in the management of patients presenting with dyspnea. However, while ultrasound equipment is readily available even in remote healthcare settings in Canada, physicians lack effective training opportunities to develop expertise in this potentially life-saving skill. To answer this critical call to action, we have developed the Accelerated Remote Consultation Tele-POCUS in Cardiopulmonary Assessment (ARCTICA) program to innovate POCUS training for today's physician leaders. This article outlines the background, research methods, and progress-to-date of ARCTICA.